The Role of Establishments and the Concentration of Occupations in Wage Inequality - Elizabeth Handwerker; James R. Spletzer (Institute for the Study of Labor (IZA), 2015)
This paper uses the microdata of the Occupational Employment Statistics (OES) Survey to assess the contribution of occupational concentration to wage inequality between establishments and its growth over time. We show that occupational concentration plays an important role in wage determination for workers, in a wide variety of occupations, and can explain some establishment-level wage variation. Occupational concentration is increasing during the 2000-2011 time period, although much of this change is explained by other observable establishment characteristics. Overall, occupational concentration can help explain a small amount of wage inequality growth between establishments during this time period.
Keywords: J31; D31; L11; D22; M12; M50; 330; occupational concentration; establishments; wage inequality; employers; employer-employee microdata